Assessing Educational Leaders : Evaluating Performance for Improved Individual and Organizational Results. - Reeves, Douglas B. (SAGE Publications, 2008)
Featuring real-world examples, this revised bestseller shows you how to improve educational leadership and organizational performance through a multidimensional leadership assessment system.